1979
DOI: 10.1099/0022-1317-45-2-263
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of a Pathogenic and an Apathogenic Strain of Newcastle Disease Virus in the Chick Embryo as Depending on the Protease Sensitivity of the Virus Glycoproteins

Abstract: SUMMARYThe pathogenic strain Italien and the apathogenic strain Ulster of Newcastle disease virus have been compared with respect to organ tropism and spread of infection in I I-day-old chick embryos. After infection of the endodermal layer of the chorioallantoic membrane by intra-allantoic inoculation with strain Italien, high virus titres are found in all extra-embryonic membranes and fluids and in the embryo itself. Infection results in early death of the embryo. In contrast, after infection with strain Uls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 13 publications
4
49
1
Order By: Relevance
“…However, F313 did not form stable oligomeric structures, its oligosaccharide chains were not modified to complex forms and are not cleaved to form F1 and F2. Our interest in investigating the phenotypic and genetic differences between the cleaved and uncleaved F proteins was based on studies on other paramyxoviruses, which have demonstrated that cleavage of the F protein is essential for fusion (Scheid & Choppin, 1977), an important determinant of virus pathogenicity (Nagai et at., 1976(Nagai et at., , 1979. Nucleotide sequence analysis and expression of chimeric F proteins created by restriction fragment exchange revealed that two amino acid differences in the F1 domain (Val to Ala at residue 301 ; Val to Met at residue 447) were responsible for the lack of F protein cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, F313 did not form stable oligomeric structures, its oligosaccharide chains were not modified to complex forms and are not cleaved to form F1 and F2. Our interest in investigating the phenotypic and genetic differences between the cleaved and uncleaved F proteins was based on studies on other paramyxoviruses, which have demonstrated that cleavage of the F protein is essential for fusion (Scheid & Choppin, 1977), an important determinant of virus pathogenicity (Nagai et at., 1976(Nagai et at., , 1979. Nucleotide sequence analysis and expression of chimeric F proteins created by restriction fragment exchange revealed that two amino acid differences in the F1 domain (Val to Ala at residue 301 ; Val to Met at residue 447) were responsible for the lack of F protein cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the length and composition of amino acids at the cleavage activation site, a stretch of hydrophilic residues that precede the N-terminal hydrophobic residues of the FI subunit, are important factors that influence the ability of paramyxovirus F proteins to be cleaved (Glickman et al, 1987;Paterson et aL, 1989;Toyoda et al, 1987). A strict correlation has been demonstrated between the ability of F proteins of 0001-0700 © 1992 SGM different strains of Newcastle disease virus to be cleaved and the extent of virus pathogenicity (Nagai et al, 1976(Nagai et al, , 1979.…”
Section: Introductionmentioning
confidence: 99%
“…Since the cleavage of the F glycoprotein occurs post-translationally and is accomplished by some protease(s) in the chorioallantoic fluid of embryonated chicken eggs (Muramatsu & Homma, 1980), in tissue culture cells (Shibuta et al, 1971 ;Silver et al, 1978) or in mouse lung (Tashiro & Homma, 1983 a), we and other authors have suggested that the presence of the activating enzyme(s) for Sendai virus will determine its host range and organ tropism (Homma, 1972b;Ishida & Homma, 1978;Silver et al, 1978). A similar proposal has been made concerning the virulence of Newcastle disease virus (Garten et al, 1980;Nagai et al, 1979).…”
mentioning
confidence: 92%
“…Past studies of paramyxoviruses have shown that proteolytic cleavage of the F 0 precursor confers infectivity, haemolytic and cell-fusing activities on virions which correlate with virulence (Scheid & Choppin, 1974Nagai et al, 1976Nagai et al, , 1979Nagai & Klenk, 1977;Fujinami & Oldstone, 1981). Our results show that the mumps F0 precursor is completely cleaved in infected cells, resulting in its absence in purified infectious virions of both non-fusing and fusing strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is based on several elegant studies using precisely defined F protein mutants of Sendai virus (Scheid & Choppin, 1976) and naturally occurring strains of Newcastle disease virus (NDV) (Nagai et al, 1976(Nagai et al, , 1979Madansky &Bratt, 1981). These studies have shown that persistence of the inactive F 0 form, either due to an inability of the host cell to cleave F 0 or to an insensitivity of the F 0 precursor to proteolytic activation, results in a limited, non-cytopathic infection.…”
Section: Introductionmentioning
confidence: 99%